Islamic Constitutional Law Perspective on Negative Campaigns in The 2024 Presidential and Legislative Elections on Social Media - Daipon, Dahyul; Amin, Saiful; Bustamar, Bustamar; Hendri, Hendri; Elfiani, Elfiani; Mak Din, Hairol Anuar (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The increasing prevalence of negative campaigns during the 2024 presidential and legislative elections on social media platforms, such as TikTok, Instagram, and Facebook, has raised concerns regarding their impact on democratic ethics and societal harmony. From the perspective of Islamic constitutional law, these campaigns are considered detrimental, aligning with the concept of ghibah and slander, which are prohibited in Islam. This study employs a descriptive-analytical approach based on library research to differentiate between negative and black campaigns. Negative campaigns use verifiable data to highlight opponents' shortcomings, while black campaigns involve unfounded accusations and slander aimed at character assassination. The research identifies key patterns in the dissemination of these campaigns: targeting young and active social media users, repetitively spreading negative content, and exploiting pseudo-legitimacy through manipulated media. The analysis highlights the inefficacy of Indonesia's Law No. 7 of 2017 in addressing these digital challenges. The findings emphasize that while negative campaigns may rely on factual data, their intent to discredit opponent conflicts with ethical and moral principles, potentially fostering division and distrust. In contrast, Islamic teachings advocate campaigns centered on virtues and constructive dialogue. This study calls for strengthened regulatory measures and public awareness to counteract the adverse effects of unethical campaign practices, ensuring the preservation of democratic integrity and societal unity.